Congenital monocular elevation deficiency associated with a novel TUBB3 gene variant. Issue 4 (13th July 2019) - Thomas, Mervyn G; Maconachie, Gail D E; Constantinescu, Cris S; Chan, Wai-Man; Barry, Brenda; Hisaund, Michael; Sheth, Viral; Kuht, Helen J; Dineen, Rob A; Harieaswar, Sreemathi; Engle, Elizabeth C; Gottlob, Irene
Abstract : Background: The genetic basis of monocular elevation deficiency (MED) is unclear. It has previously been considered to arise due to a supranuclear abnormality. Methods: Two brothers with MED were referred to Leicester Royal Infirmary, UK from the local opticians. Their father had bilateral ptosis and was unable to elevate both eyes, consistent with the diagnosis of congenital fibrosis of extraocular muscles (CFEOM). Candidate sequencing was performed in all family members. Results: Both affected siblings (aged 7 and 12 years) were unable to elevate the right eye. Their father had bilateral ptosis, left esotropia and bilateral limitation of elevation. Chin up head posture was present in the older sibling and the father. Bell's phenomenon and vertical rotational vestibulo-ocular reflex were absent in the right eye for both children. Mild bilateral facial nerve palsy was present in the older sibling and the father. Both siblings had slight difficulty with tandem gait. MRI revealed hypoplastic oculomotor nerve. Left anterior insular focal cortical dysplasia was seen in the older sibling. Sequencing of TUBB3 revealed a novel heterozygous variant (c.1263G>C, p.E421D) segregating with the phenotype. This residue is in the C-terminal H12 α-helix of β-tubulin and is one of three putative kinesin binding sites. Conclusion: We show that familial MED can arise from a TUBB3 variant and could be considered a limited form of CFEOM. Neurological features such as mild facial palsy and cortical malformations can be present in patients with MED. Thus, in individuals with congenital MED, consideration may be made for TUBB3 mutation screening.